Agri-environmental measures and the breeding ecology of a declining farmland bird. (August 2017) - McHugh, Niamh M.; Prior, Matt; Grice, Philip V.; Leather, Simon R.; Holland, John M.
Abstract: Agricultural intensification is a key cause of the population declines shown by many farmland bird species across Europe. Changes in land management through agri-environment schemes (AES) are frequently cited as the best tool to reverse these trends, to date however they have received mixed support. This study tested whether AES options in England that provide winter seed food or insect-rich foraging during the breeding season, were associated with improved breeding performance in tree sparrow, Passer montanus, and/or the formation of larger breeding colonies. Breeding attempts (n = 428) representing 210 pairs of tree sparrow comprising 22 colonies were compared in Wiltshire, England in 2013 and 2014. The area of margin AES, an insect-rich habitat, was positively correlated with fledgling success per breeding attempt and per breeding pair. Colony size increased with increasing wild bird seed mix AES area, a winter seed food resource, but this option negatively affected hatching success and the number of fledglings produced per breeding attempt. The observed association between colony size and this habitat was expected given that wild bird seed mixtures provide important seed food resources for granivorous birds during winter. The negative correlation with fledgling success, on the other hand, requires further investigation to determine whether this relationship relates to a lack of invertebrate and seed food during the breeding period. These results highlight the importance of providing a suite of AES habitats that are appropriately located to deliver both overwintering and breeding requirements of target, declining farmland birds.